Pengaruh Likuiditas terhadap Struktur Modal pada Perusahaan MLBI yang Terdaftar di Bursa Efek Indonesia Tahun 2014 - 2024 - Gulo, Yanto Nius; Faruq, Ahmad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of liquidity on capital structure at PT Multi Bintang Indonesia Tbk, which is listed on the Indonesia Stock Exchange (IDX), during the period 2014–2024. The research approach used is a quantitative associative method by utilizing secondary data in the form of the company’s annual financial statements. The research population includes all financial data of PT Multi Bintang Indonesia Tbk over eleven years, which are also used as the research sample. Data processing was carried out using SPSS software version 27 through simple linear regression analysis. the results show that the correlation coefficient (R) is 0.791, indicating a strong relationship between the liquidity variable and capital structure. The coefficient of determination (R²) of 0.625 indicates that 62.5% of the variation in capital structure can be explained by liquidity, while the remaining 37.5% is influenced by other factors outside the research model. Partial hypothesis testing produces a liquidity regression coefficient of -3.104 with a significance level of 0.004, meaning that liquidity has a significant effect on capital structure. This negative relationship indicates that an increase in liquidity tends to be followed by a decrease in capital structure. these findings suggest that the level of liquidity plays an important role in corporate financing decision-making. Therefore, management needs to pay close attention to optimal liquidity management in order to achieve an efficient and sustainable capital structure. This study is expected to provide theoretical and practical contributions to the development of corporate financial policies.